A Hybrid Model for Green Supplier Selection and Order Allocation: DEMATEL, ANP, and Multi-criteria Goal Programming Approach - Dana Marsetiya Utama; Anindya Apritha Putri; Ikhlasul Amallynda (Jurnal Optimasi Sistem Industri, 2021)
Increased competition in the industrial world forces companies to increase their competitiveness through Green Supply Chain Management (GSCM). The key to the success of GSCM is the selection of suppliers and the allocation of the proper order by taking into account environmental aspects. This decision involves several criteria and must also pay attention to the relationship between criteria. This study proposes a hybrid procedure to solve Green Supplier Selection and Order Allocation (GSSOA). The integration of Decision Making Trial and Evaluation Laboratory (DEMATEL), Analytic Network Process (ANP), and Multi-Criteria Goal Programming (MCGP) are proposed to solve this problem. The DEMATEL is used to calculate the relationship between criteria. Furthermore, the ANP is proposed to determine the weight of the criteria and supplier ranking. Finally, the MCGP method is offered for allocating orders based on priority suppliers. A case study on the food industry in Malang, Indonesia, was conducted to apply this procedure. The results showed that the low defects rate criterion is the most important compared to other criteria. The best supplier was successfully selected, and the order allocation was completed. Order allocation priority is to suppliers D, C, A, and B. This study also presents a sensitivity analysis for order allocation.